Talent management strategy and absorptive capacity as antecedences of innovation capability: A conceptual framework - Aljanabi, AbdulQadir Rahomee Ahmed; Kumar M., Dileep (The International Journal Research Publications Pte. Ltd, 2013)
The purpose of this paper is to examine how the strategy of talent management (TM) and absorptive capacity can affect innovation capability.This paper reviewed related literature with these concepts and then submits a proposed theoretical framework to manifest the relationship between these variable. Innovation has so far constantly considered from a Knowledge management (KM) perspective; this paper examines the innovation and innovation capability from absorptive capacity and TM strategy perspective as a critical success factors and concluded how organizations can benefit from the integration of TM strategy and absorptive capacity principles to develop innovation capability and achieve a high level of performance.